FACTORS INFLUENCING THE CHILD LANGUAGE DEVELOPMENT - Kuzina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Childhood is the basis for both life and language acquisition. The child language is greatly influenced by the language environment – parents and other family members, teachers, as well as movies, TV and radio broadcasting, theatre performances, books. Meanwhile exploring the world and characterizing it, the child gradually acquires the skill to use in its language synonyms, antonyms, phraseology, comparisons, learns to understand foreign origin words used on daily basis, etc.In order to establish, which factors are influencing positively the child language development, a questionnaire was worked out. Students, general education school teachers, as well as the preschool education teachers completed the questionnaire. The research on the factors influencing the children's language development was accomplished in the framework of the Norwegian project in 2015. The results of the questionnaire and opinion polls prove, the childhood stage is very significant in the child language development, and really great is the responsibility of adults (parents and teachers), to ensure that this process develops as valid, interesting and exciting for the child. One of the conditions for successful acquisition of the Latvian language vocabulary stock is the example shown by the speech of adults. The use of illiterate language must also be eliminated from schools, mass media, etc.